The Role of Sports Teachers and Coaches in Improving Student Athletes' Achievement - Siska Aprelyani (Siber International Journal of Sport Education, 2026)
Literature Review of the Role of Sports Teachers and Coaches in Improving Student Athlete Achievement is a scientific article with the aim of analyzing whether student athlete achievement plays a role in sports teachers and coaches. The method examines various studies, articles, and books relevant to the topic discussed. The results of this article are: 1) Sports Teachers play a role in Athlete Achievement; 2) Coaches play a role in Athlete Achievement. In addition to these two exogenous variables that influence the endogenous variable of Athlete Achievement, there are still many other factors including talent, physical condition, mental health.